Matthew Lipman’s method against the indoctrination - Rusek, Damian (Hybris, 2015)
Nowadays, the problem of indoctrination at schools seems to be quite distant and invalid in the sphere of the pedagogical research. It appears that manipulating students and inculcating certain attitudes and beliefs to them may often be conducted unconsciously, which suppresses students’ remarkable capacities such as critical thinking, frank expression of their own opinions and much broader view on the varied subjects at the same time. The method of M. Lipman appears to be an effective solution for eliminating indoctrination at schools and adopting above mentioned attitudes by the students. After defining and analyzing certain notions concerning indoctrination and education, I present strong and weak points of the method of M. Lipman in excluding the idea of indoctrination at schools. The following writing presents the meaning and the significance of “The Philosophy for Children” in the struggle against the indoctrination.